2014
DOI: 10.1021/np400633m
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Protein Kinase Inhibiting Nakijiquinones and Nakijiquinols from the Sponge Dactylospongia metachromia

Abstract: Chemical investigation of the sponge Dactylospongia metachromia afforded five new sesquiterpene aminoquinones (1-5), two new sesquiterpene benzoxazoles (6 and 7), the known analogue 18-hydroxy-5-epi-hyrtiophenol (8), and a known glycerolipid. The structures of all compounds were unambiguously elucidated by one- and two-dimensional NMR and by MS analyses, as well as by comparison with the literature. Compounds 1-5 showed potent cytotoxicity against the mouse lymphoma cell line L5178Y with IC50 values ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 52 publications
3
40
0
Order By: Relevance
“…Merosesquiterpenoids 899-930 came from the sponge genera Aka (Siphonodictyon), Dysidea, Dactylospongia and Xestosopngia. [578][579][580][581][582][583][584] In particular, xestolactone A 931 and xestosaprol O 932 were isolated from Xestospongia vansoesti (Palawan Is., Philippines). Xestosaprol O is twenty times more potent as an inhibitor of indoleamine 2,3dioxygenase (IDO; IC 50 ¼ 4 mM) than 931 (IC 50 ¼ 81 mM), making it a lead towards inhibitors of tumour immune escape.…”
Section: Spongesmentioning
confidence: 99%
“…Merosesquiterpenoids 899-930 came from the sponge genera Aka (Siphonodictyon), Dysidea, Dactylospongia and Xestosopngia. [578][579][580][581][582][583][584] In particular, xestolactone A 931 and xestosaprol O 932 were isolated from Xestospongia vansoesti (Palawan Is., Philippines). Xestosaprol O is twenty times more potent as an inhibitor of indoleamine 2,3dioxygenase (IDO; IC 50 ¼ 4 mM) than 931 (IC 50 ¼ 81 mM), making it a lead towards inhibitors of tumour immune escape.…”
Section: Spongesmentioning
confidence: 99%
“…Detailed analysis of 1 D and 2 D NMR data suggested that 9 possessed the same terpenoid quinone moiety (C‐1 to C‐21) as that of 4 as well as the presence of characteristic signals corresponding to the above mentioned 3‐(methylsulfinyl)propan‐1‐amine spin system. Furthermore, the 13 C NMR spectrum showed characteristic resonances corresponding to a phenethylamine unit . Observed HMBC correlation from H 2 ‐22 to C‐18 established the location of the 3‐(methylsulfinyl)propan‐1‐amine residue at C‐18.…”
Section: Resultsmentioning
confidence: 93%
“…A derivative of oleanolic acid triterpene, namely, 3,21-dioxo-olean-18-en-oic acid (126) (Fig. Recently, additional natural nakijiquinone derivatives with potent protein kinase inhibitory activity were isolated from a marine sponge, Dactylospongia metachromia [227]. The triterpene 126 was an inhibitor of tyrosine kinase (Tie2 kinase) with the IC 50 value of 4.2 mM; however, it showed only modest cytotoxic activity against cultured mammalian cells [216].…”
Section: Inhibitors Of Tyrosine Kinases As Anticancer Agentsmentioning
confidence: 99%
“…Many plants Reversible inhibitor and suppression of VEGFR-2 [197][198][199] Hematoxylin (118) Inhibiting Her-2/neu kinase, EGFR, and VEGFR-2; however, detailed mechanism of action has not yet been reported [224][225][226][227] activity could therefore lead to the growth inhibition of cancer cells, and it is a potential approach for cancer therapy [248].…”
Section: Mechanism Of Action Referencesmentioning
confidence: 99%